Culture-Centred Exercises for Teaching Basic Group Microskills - Pedersen, Paul B. (Canadian Journal of Counselling and Psychotherapy, 2007)
Ten basic group microskills are defined, and matched with experiential and multicultural training exercises for teaching helping skills to group workers. Guidelines for debriefing are offered to help instructors fit the exercises into their teaching or training design. It is argued that these exercises will provide an opportunity to include community resource persons in the multicultural training process and by mobilizing the diverse backgrounds of students within the training setting as a teaching resource. The unique advantage of using microskills in training group workers is highlighted.